2016
DOI: 10.1182/blood-2015-05-648550
|View full text |Cite
|
Sign up to set email alerts
|

Arf6 controls platelet spreading and clot retraction via integrin αIIbβ3 trafficking

Abstract: • Arf6 selectively regulates endocytic trafficking of platelet a IIb b 3 .• Endocytosis contributes to acute platelet function.Platelet and megakaryocyte endocytosis is important for loading certain granule cargo (ie, fibrinogen [Fg] and vascular endothelial growth factor); however, the mechanisms of platelet endocytosis and its functional acute effects are understudied. Adenosine 5'-diphosphate-ribosylation factor 6 (Arf6) is a small guanosine triphosphate-binding protein that regulates endocytic trafficking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 36 publications
2
64
0
1
Order By: Relevance
“…These findings are consistent with Kanamarlapudi and colleagues who showed that Arf6 regulates P2Y trafficking in platelets as well as dynamin-dependent fission of coated vesicles during endocytosis[50]. Additionally, two Rab proteins (Rab4 and Rab11) are also involved in integrin-mediated fibrinogen uptake and trafficking in platelets[49, 51]. …”
Section: Granular Secretion Mechanisms In Plateletssupporting
confidence: 87%
See 1 more Smart Citation
“…These findings are consistent with Kanamarlapudi and colleagues who showed that Arf6 regulates P2Y trafficking in platelets as well as dynamin-dependent fission of coated vesicles during endocytosis[50]. Additionally, two Rab proteins (Rab4 and Rab11) are also involved in integrin-mediated fibrinogen uptake and trafficking in platelets[49, 51]. …”
Section: Granular Secretion Mechanisms In Plateletssupporting
confidence: 87%
“…Endocytosis is an important process in platelets and megakaryocytes for loading certain granule cargo, such as fibrinogen (Fg) and vascular endothelial growth factor (VEGF)[4648]. While the mechanisms of platelet endocytosis remain incompletely understood, recent studies demonstrate that adenosine 5′-diphosphate–ribosylation factor 6 (Arf6), a small guanosine triphosphate-binding protein, regulates integrin α2bβ3 trafficking and fibrinogen uptake[49]. Genetic ablation of Arf6 in platelets enhanced clot retraction and spreading, indicating that endocytosis contributes to rapid platelet functions.…”
Section: Granular Secretion Mechanisms In Plateletsmentioning
confidence: 99%
“…141 Integrins can also crosstalk with other cell-surface proteins/receptors to mediate outside-in signaling, and a IIb b 3 makes functionally important interactions with tetraspanins such as CD151 and tumor-suppressing subchromosomal transferable fragment cDNA 6 (TSSC6). 23,142,143 The small GTPase Arf6 can regulate a IIb b 3 trafficking, 144 and many further proteins are likely to be involved in this important, yet understudied, aspect of a IIb b 3 biology.…”
mentioning
confidence: 99%
“…ADP‐ribosylation factor 6 (Arf6) belongs to the Arf family of small G‐proteins and is involved in receptor trafficking in platelets 97. In contrast to Rap1, Rac1, and RhoA, Arf6 is inhibited during platelet activation, whereas cyclic nucleotide pathways elevate Arf6‐GTP levels 98.…”
Section: Interactions Involving Small G‐proteinsmentioning
confidence: 99%